Regulation of matrix metalloproteinases-8, -9 and endogenous tissue inhibitor-1 in oral biofluids during pregnancy and postpartum. (April 2021) - Özgen Öztürk, V.; Meriç, Pınar; Sorsa, Timo; Tervahartiala, Taina; Bostanci, Nagihan; Nwhator, Solomon O.; Emingil, Gülnur
Highlights: Pregnant/postpartum women had higher saliva/GCF MMP-8 and MMP-9 than controls. Gingivitis patients within groups had higher saliva/GCF MMP-8 and MMP-9 than controls. Non-pregnant women exhibited lower TIMP-1 in saliva than the postpartum group. Abstract: Objective: During pregnancy, mothers undergoe considerable physiological changes affecting the whole body including periodontal tissues. Susceptibility to gingival inflammation during pregnancy could be mediated by modulation of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). Therefore, the aim of this study was to investigate salivary and gingival crevicular fluid (GCF) levels of MMPs and TIMPs during the second and third trimester of pregnancy and postpartum. Design: Saliva and GCF samples were collected from 96 pregnant women (PW) before and after giving birth. The sixty matched non-pregnant women (N-PW) were recruited as a control group and full-mouth periodontal examination was performed. The levels of MMP-8, MMP-9 and TIMP-1 were determined by immunofluorometric and enzyme-linked immunosorbent assays. Results: The PW group exhibited significantly higher levels of MMP-8 and MMP-9 in their saliva than the N-PW group while corresponding salivary TIMP-1 levels were significantly lower in NPW compared to the postpartum stage. This resulted in significantly higher MMP-8/TIMP-1 and MMP-9/TIMP-1ratio in the saliva from PW before and after birth than in that from N-PW. MMP-8, MMP-9 and TIMP-1 levels were higher in GCF from PW and postpartum than in that from N-PW. Conclusions: MMP-8 and MMP-9 levels in saliva and GCF reflect inflammatory burden during pregnancy. They could be used for monitoring the inflammatory state of gingival tissues during pregnancy.